Use of fly ash as synergistic and reactive component of flame retardant system in polylactide. (May 2023) - Batistella, Marcos; Roux, Jean-Claude; le Saout, Gwenn; Callone, Emanuela; Diré, Sandra; Xenopoulos, Constantinos; Lopez-Cuesta, José-Marie
Highlights: Fly ash (FA) and flame retardants were evaluated to fire retard polylactide. Partial substitution of FR systems by FA allowed to improve the fire performance. Interactions between flame retardants and FA were observed and new components are identified by XRD and NMR. Abstract: For a long time, fly ash has been considered as pure waste of coal power plants. Nevertheless, unique properties and compositions that vary with the material's origin make fly ash appealing as an engineering material in various applications. Thus, the opportunity to reduce the environmental footprint of polylactide through the incorporation of fly ash as a component of flame retardant systems has been investigated. Combinations of fly ash with ammonium polyphosphate and/or melamine polyphosphate were made for a global loading of 25 wt% with various rates of substitution of the flame retardants. Fire performance has been studied from cone calorimeter experiments as well as the use of pyrolysis combustion flow calorimeter (PCFC) and the UL94V test. The interpretation of the fire retardant mechanisms has been performed through the examination of cone calorimeter residues by scanning electronic microscopy, X-ray microanalysis, X-ray diffraction (XRD) and multinuclear solid-state NMR. It can be shown that fly ash is mainly composed of spherical particles which are thermally stable at cone calorimeter tests when used alone in PLA. Conversely, fly ash behaves as a reactive component with both flame retardants, leading to the formation of new crystalline and amorphous compounds as shown by XRD and NMR. Synergistic effects in fire performance resulting from the reactive behavior of fly ash can be highlighted and are ascribed to fire retardant mechanisms acting in the condensed phase, and corresponding to the conservation of high phosphorus contents in the condensed phase.